1996
DOI: 10.1209/epl/i1996-00407-y
|View full text |Cite
|
Sign up to set email alerts
|

6 He + α clustering in 10 Be

Abstract: Abstract. -In a kinematically complete measurement of the 7 Li( 7 Li,α 6 He)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 16 publications
4
30
0
Order By: Relevance
“…Recently, contributions of such higher shells were analyzed in Nϭ8 nuclei. A calculation based on the shell model has shown that the slow ␤ decay of 12 Be to 12 B can be explained by an admixture of the sd shell in 12 Be (Nϭ8) in which the closed p-shell component must be less than 30% ͓4͔. This shows that the concept of magic numbers is vague in 12 Be.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, contributions of such higher shells were analyzed in Nϭ8 nuclei. A calculation based on the shell model has shown that the slow ␤ decay of 12 Be to 12 B can be explained by an admixture of the sd shell in 12 Be (Nϭ8) in which the closed p-shell component must be less than 30% ͓4͔. This shows that the concept of magic numbers is vague in 12 Be.…”
Section: Introductionmentioning
confidence: 99%
“…A calculation based on the shell model has shown that the slow ␤ decay of 12 Be to 12 B can be explained by an admixture of the sd shell in 12 Be (Nϭ8) in which the closed p-shell component must be less than 30% ͓4͔. This shows that the concept of magic numbers is vague in 12 Be. In the case of light nuclei, it has been shown that cluster structure appears in the vicinity of a threshold energy ͓5,6͔.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the presence of rotational bands with the α-α structure in the excited states of 10 Be and 12 Be and the breaking of the magic number (N = 8) due to the clustering of the core have attracted much attention [9][10][11][12][13][14][15][16]. We have suggested, based on the molecular-orbit model, that these phenomena can be well explained by introducing single-particle orbits around the α-α cluster structure [15].…”
mentioning
confidence: 99%
“…[13]), with associate states finally clearly established in 10 Be [14,15] as a rotational band starting with the 0…”
Section: Introductionmentioning
confidence: 99%